Virtual Reality in Destination Marketing: The Why, The Who and The When - PRODAN, Sergiu Grigore; EGRESI, István (Studia Universitatis Babeș-Bolyai Geographia, 2023)
Virtual reality (VR) is one of the fastest growing areas in information and communication technologies. Starting with the 1990s, the technology has also been successfully employed in tourism. Among other purposes, VR is used in tourism to provide a more effective marketing of a destination than classical means such as (paper) brochures. While the literature on the use of VR in destination marketing has been steadily growing, it is still scarce and fragmented. The main objective of this study is to better understand how could VR be used to improve the marketing of tourism destinations. To gather data for this study an experiment was used: participants were invited to take an online virtual tour of a very popular landmark in Paris, and then fill out a questionnaire in order to share their experience. The data from the 89 questionnaires collected were then processed using SPSS. The results have shown that almost all of our respondents were satisfied with their VR experience. Moreover, the VR experiment has improved the users’ image of and satisfaction with the destination. This, in turn, has positively influenced their intention to visit or re-visit the destination and to recommend it to others. The study also found that some socio-demographic groups (female, older than 25 years) may be more suitable targets for destination marketing using VR than others. Finally, we learned that, although the use of VR is effective for destination marketing both before and after tourists visit the site, the technology may be more useful in improving the image of the destination when applied before the physical visit.